Contributors to Electronic Health Record-Integrated Secure Messaging Use: A Study of Over 33,000 Health Care Professionals - Baratta, Laura R.; Lew, Daphne; Kannampallil, Thomas; Lou, Sunny S. (Applied Clinical Informatics, 2024)
Objectives Electronic health record (EHR)-integrated secure messaging is extensively used for communication between clinicians. We investigated the factors contributing to secure messaging use in a large health care system.Methods This was a cross-sectional study that included 14 hospitals and 263 outpatient clinic locations. Data on EHR-integrated secure messaging use over a 1-month period (February 1, 2023, through February 28, 2023) were collected. A multilevel mixed effects model was used to assess the contribution of clinical role, clinical unit (i.e., specific inpatient ward or outpatient clinic), hospital or clinic location (i.e., Hospital X or Outpatient Clinic Building Y), and inpatient versus outpatient setting toward secure messaging use.Results Of the 33,195 health care professionals who worked during the study period, 20,576 (62%) were secure messaging users. In total, 25.3% of the variability in messaging use was attributable to the clinical unit and 30.5% was attributable to the hospital or clinic location. Compared with nurses, advanced practice providers, pharmacists, and physicians were more likely to use secure messaging, whereas medical assistants, social workers, and therapists were less likely (p < 0.001). After adjusting for other factors, inpatient versus outpatient setting was not associated with secure messaging use.Conclusion Secure messaging was widely used; however, there was substantial variation by clinical role, clinical unit, and hospital or clinic location. Our results suggest that interventions and policies for managing secure messaging behaviors are likely to be most effective if they are not only set at the organizational level but also communicated and tailored toward individual clinical units and clinician workflows.
Keywords: communication; electronic health records; adoption of new technology; secure messaging; interprofessional communication